Knowledge, attitude towards, and utilization of friendly health services among school adolescents in the pastoral community of Guji zone, Ethiopia: an institution-based comparative cross-sectional study - Godana, Gobena; Garoma, Silesh; Ayers, Nicola; Abera, Muluembet (Frontiers in Reproductive Health, 2024)
AimAlthough sexual and reproductive health for adolescents is a recognized fundamental human right and a critical component of health policy, it is poorly addressed and seldom researched in pastoral communities. The study aimed to determine the status of sexual and reproductive health knowledge, attitudes, and practice among pastoral school adolescents in Ethiopia.Study designAn Institution-based comparative study was conducted from Nov. 2020 to Jan. 2021.MethodsWe conducted a comparative cross-sectional study at four randomly selected high schools. Seven hundred seventy-three adolescent students participated, with 384 from Gorodola and 389 from Wadara districts, Guji zone Ethiopia. The data was collected using 34 self-administered questions and analyzed using descriptive, t-test, and linear regression models.ResultsThe study found that only 44.2% of all the participants had good knowledge, 46.1% had good attitudes and 35.4% had good utilization of Sexual and Reproductive Health Services. Respondents from Wadara High School had significantly higher mean knowledge scores (49.3% vs. 44.2%, p < 0.01) than those of Gorodola High School. There was no significant difference in mean utilization scores between case and compare (45.08% vs. 37%, p > 0.01). Adolescents who were not communicated on SRH matters, previously utilized FHS, and visited Friendly Health facilities were associated with poor utilization of sexual and reproductive health services.Conclusion and public health contributionsWadera High School adolescents have better Sexual and reproductive health knowledge and utilization than Gorodola high schools. Community public health care providers in Wadara District explain the outcome through their contributions. Within the context of inherent disadvantage in the school environment setting, there is a need to improve sexual and reproductive health education with a greater emphasis on school girls.